PAINTING AS THE LANGUAGE OF UDMURT NATIONALITY CULTURE - A.N. Utekhina (Многоязычие в образовательном пространстве)
The development of cultural values of any nationality suggests not just the study of written records or oral folk art, it also involves the knowledge of musical art and painting. It is very important for the successful educational process and cross-cultural interaction. The creative work of V.N. Morozov, an Honoured Artist of the Udmurt Republic, twice a laureate of the State Prize, may serve as a vivid example. V.N. Morozov is a universal artist, which is manifested in his artistic and educational activities: picturesque landscapes of the native countryside, book graphics, including illustrations for the works of famous Udmurt scholars and writers, religious paintings, in which the artist reinterprets the canonical images of church art, based on his rich research experience and his own worldview. His creativity is multifaceted and multidimensional; it is permeated with his love of the native land, the people who raised him, and the nature which inspired him. The artist himself is a gold mine of Udmurt mentality: wisdom, industriousness, mastery and kindness.